2013
DOI: 10.1111/pim.12024
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of aDNAvaccine encoding theToxoplasma gondiicyclophilin gene inBALB/cmice

Abstract: Toxoplasmosis is a world-wide zoonosis that causes significant public health and veterinary problems. The study of vaccines remains the most promising method for the future prevention and control of toxoplasmosis. Recombinant Toxoplasma gondii cyclophilin has been shown to have potent PPIase and IL-12-inducing activities, thus promoting the stabilization of T. gondii's life cycle and maintaining the survival of its host during evolution. In this study, the T. gondii cyclophilin gene was used to construct a DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In many studies regarding development of vaccines against T. gondii , encouraging outcomes were obtained when the antigens were delivered as DNA vaccines . In this research, DNA vaccination with TgMDH demonstrated significant results; however, comparisons between the immunological changes and protection induced by TgMDH as DNA vaccine and recombinant protein need to be further researched.…”
Section: Discussionmentioning
confidence: 82%
“…In many studies regarding development of vaccines against T. gondii , encouraging outcomes were obtained when the antigens were delivered as DNA vaccines . In this research, DNA vaccination with TgMDH demonstrated significant results; however, comparisons between the immunological changes and protection induced by TgMDH as DNA vaccine and recombinant protein need to be further researched.…”
Section: Discussionmentioning
confidence: 82%
“…The in vitro transfection assay was performed as previously described [41]. Briefly, before transfection, 2 × 10 4 HEK293T cells were seeded in a 6-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past 4 years, toxoplasmosis DNA vaccination studies expanded to the use of many new parasite antigens, several of which yielded promising protective outcomes ( Table 2 ). Among these latest developments, several single-antigen vaccines were successful in producing survivors from a lethal infection challenge, such as ROP8, TgCyP, and GRA6 with a range of survival rate between 37.5-50.0% [ 52 , 53 , 54 ]. Another subset of these DNA vaccine studies produced a significant increase in survival time (≥3 weeks) but no survivors following a lethal challenge, which was the ROP13, ROP16, ROP18, MIC13, and eIF4A [ 34 , 36 , 55 , 56 , 57 ].…”
Section: Dna Vaccinesmentioning
confidence: 99%